2 Cholesterol crystal secretion of IL-1β from PBMCS is reduced with simvastatin treatment. (26th March 2018) - Gangadharan, N; Kavanagh, P; Wash, PT; Hemeryck, L; Kieran, J; Barry, M; Lucitt, M
Abstract : Considerable evidence implicates a role for interleukin-1 beta (IL-1β) in the pathogenesis of atherosclerosis 1 revealing its potential as a novel therapeutic target. Statins are known to have anti-inflammatory effects, 2 however the specific mechanisms remain to be established. To test the anti-inflammatory effects of simvastatin, PBMCs were isolated from healthy donors and treated in vitro with simvastatin (100 µM) or from hyperlipidaemic patients at baseline and following 8 weeks simvastatin (10–20 mg) daily treatment. PBMCs were then stimulated with LPS (100 ng/ml) for 3 hour followed by cholesterol crystal (CC) (1 mg/ml) stimulation overnight to activate the NLRP3 inflammasome complex involved in processing IL-1β to its mature secreted form. IL-Iβ levels in the supernatants form PBMCs was measured by ELISA. All experiments carried out were approved by the Medical Research Ethics Committees at St James Hospital/AMNCH, Dublin 8, Ireland and comply fully with the Declaration of Helsinki. Patients (n=9) taking simvastatin (10–20 mg daily) over 8 weeks exhibited reduced LDL cholesterol, (4.87±0.76 mmol/L) pre vs (3.78±0.67 mmol/L) post statin treatment. Simvastatin treatment also reduced levels of IL-1β secretion by PBMCs, when stimulated with LPS and CC, (5.27±0.6 ng/ml) pre vs (4.27±0.5 ng/ml) post statin treatment. Similarly, in vitro treatment of PBMCs with simvastatin (100 µM) reduced IL-1β secretion upon activation with LPS and CC, (2.37±0.17 ng/ml) control vs (0.64±0.06 ng/ml) simvastatin treatment. Values presented are mean ±sem. We have demonstrated that CC induced IL-1β release by PBMCs from hyperlipidaemic patients, is reduced after treatment with simvastatin. These data identify a previously unappreciated beneficial role for statin therapy in atherosclerotic patients. References: . Duewell P, et al. Nature2010;464:1357–61. . Arslan F, et al. Circ Res2008;103:334–6.